Survival in HIV‐infected patients with lymphoma according to the choice of antiretroviral treatment: an observational multicentre study. Issue 8 (4th June 2018) - Focà, E; Cavaglià, G; Rusconi, S; Cascavilla, A; Cenderello, G; Re, A; Casari, S; van den Bogaart, L; Zinzani, PL; Caracciolo, D; Di Perri, G; Bonito, A; et al.
Abstract : Objectives: Lymphoproliferative disorders are often observed in HIV‐positive patients. Combination antiretroviral treatment (cART) during antineoplastic chemotherapy is beneficial, but little is known about the clinical outcome according to different antiretroviral combinations. The aim of the study was to address this gap in current knowledge. Methods: A retrospective study was conducted in five large Italian centres for the period from 1998 to 2015; HIV‐positive patients diagnosed with lymphoma were included and demographic, clinical and therapeutic variables were recorded and associated with clinical outcomes. Bivariate and multivariate analyses were performed, including Cox proportional hazard models for survival. Results: A total of 399 patients were included in the study. The most common types of lymphoma were diffuse large B‐cell lymphoma (DLCLB; n = 164), Hodgkin lymphoma (HL; n = 99) and Burkitt lymphoma (BL; n = 57), followed by plasmablastic lymphoma (PBL; n = 38), T‐cell lymphoma (TCL; n = 17), indolent lymphoma ( n = 10) and other less common types ( n = 14). cART was given to 327 (out of 387 evaluable) patients: in 216 subjects it was protease inhibitor (PI)‐based, in 73 it was nonnucleoside reverse transcriptase inhibitor (NNRTI)‐based and in 18 it was integrase strand transfer inhibitor (INSTI)‐based (the remaining 20 individuals received other regimens). The 5‐year overall survival was 57.5% (52.8% for DLCLB, 67.8% for HL, 42.3% for BL, 60.6% for PBL and 64.7% for TCL). PI‐based ART compared with other compounds was associated with worse survival in non‐Hodgkin lymphoma (NHL) and HL patients combined ( P ≤ 0.001) and in NHL patients alone ( P < 0.001); grade 3–4 haematological toxicities were more commonly observed in PI‐treated individuals. Lymphoma diagnosis in recent years, better immunovirological status, lower lymphoma stage and better prognostic indexes were associated with better survival. Conclusions: PI‐based cART while on chemotherapy was associated with worse overall survival and more frequent haematological complications in HIV‐positive patients with lymphoma.